1984
DOI: 10.1002/chin.198417004
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: EFFECT OF LATTICE DEFECTS IN IRON ON HYDROGEN DIFFUSION

Abstract: Mit Hilfe elektrochemischer Permeationsmessungen werden der Diffusionskoeffizient, der Permeationskoeffizient und die Löslichkeit von H in Fe zwischen 0 und 80°C ermittelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
1
12
0
2
Order By: Relevance
“…71 A more computationally intensive, atomistic approach on -iron was reported by Psiachos, who also found a similar enhancement of H solubility in the tensile strain region immediately below the glide plane of an edge dislocation. 73 This DFT study reported enhancement of hydrogen binding energies in iron (equivalently, "solution energies") with tensile hydrostatic strain, approaching 0.56 eV at -0.02 in the dilute limit (i.e., dissolved H content approaching zero); 73 this calculated value compares favorably to those obtained experimentally by Kumnick and Johnson (0.62 eV) 69 and Riecke and Bohnenkamp (0.58 eV) 74 on cold-worked, high-purity iron. From internal friction measurements on cold-worked iron, lower H-dislocation energy values were inferred by Gibala (0.28 eV), 75 and Zielinski and coworkers (~0.3 eV).…”
supporting
confidence: 73%
“…71 A more computationally intensive, atomistic approach on -iron was reported by Psiachos, who also found a similar enhancement of H solubility in the tensile strain region immediately below the glide plane of an edge dislocation. 73 This DFT study reported enhancement of hydrogen binding energies in iron (equivalently, "solution energies") with tensile hydrostatic strain, approaching 0.56 eV at -0.02 in the dilute limit (i.e., dissolved H content approaching zero); 73 this calculated value compares favorably to those obtained experimentally by Kumnick and Johnson (0.62 eV) 69 and Riecke and Bohnenkamp (0.58 eV) 74 on cold-worked, high-purity iron. From internal friction measurements on cold-worked iron, lower H-dislocation energy values were inferred by Gibala (0.28 eV), 75 and Zielinski and coworkers (~0.3 eV).…”
supporting
confidence: 73%
“…A fit close to ⌬H s the enthalpy of solution, for iron 5 ϫ 10 23 m Ϫ3 Pa Ϫ1/2 their observations (Figure 2 also) is and 28.6 kJ/mol, respectively. [22] At low hydrogen pressures, the hydrogen gas can be regarded as an ideal gas and the log N T ϭ 23.3 Ϫ 2.33e Ϫ4.0 p [27] fugacity may be replaced by the pressure p, which leads to Eq. [1].…”
Section: B Void Trapsmentioning
confidence: 99%
“…Die Einfliisse der Legierungselemente und deren Karbide auf die Aufnahme, Diffusion und Anreicherung von Wasserstoff in Eisen wurden rnit Hilfe der elektrochemischen Permeationsmethode [2] untersucht . Die Wasserstoffaufnahme erfolgte entweder aus der Gasphase bei Wasserstoffpartialdriicken von p~~ = 1; 0,36; 0,05 oder 0,Ol bar oder elektrolytisch, in 0,l N NaOH/N2 oder (1 M H2S04 + M AszO3)/Nz, unter Vorgabe konstanter Kathodenstromdichten i K = -1 bis -10 mA/cm2.…”
Section: Experimentellesunclassified
“…N' kann nach (10) und (11) mit Hilfe der Daten fiir N$ und AH: von Tabelle2 berechnet werden. Mit co von[2] und @L = 1 -@ ; , da 0; < 1, ergibt sich c$(Abb, 4). Das Produkt aus effektiver Liislichkeit und dem Diffusionskoeffizienten unter ,,trapping"-EinfluB beschreibt den H-Permeationskoeffizienten, = c : 'DT, der nur die Wirkung der flachen ,,traps" auf die stationare H-Permeation berucksichtigt.…”
unclassified